A new strategy to define consortium sanitary landfill siting location based on multicriteria analysis - Pinheiro, Mayara Maezano Faita; Osco, Lucas Prado; Mendes, Tatiana Sussel Gonçalves [UNESP]; Cicerelli, Rejane Ennes; Ramos, Ana Paula Marques (Revista Brasileira de Geografia Fisica, 2021)
The area selection process for sanitary landfills can be performed with a Multicriteria Decision Analysis (MCDA) in a GIS-environment. However, environmental variables need to be properly model before any MCDA is performed. One manner to perform this is to integrate MCDA with Fuzzy Inference. Still, to the best of our knowledge, this strategy was not evaluated in the selection of areas for consortium landfills. Here, we propose a new framework to select consortium landfill areas by integrating MCDA and Fuzzy logic with environmental and socioeconomic features in GIS environment. For this, we considered multiple levels of social-environmental suitability to attend a large and a small number of cities in a 20-years period. A region in the interior of São Paulo, Brazil, with 32 municipalities was selected as study area and the Weighted Linear Combination (WLC) method was applied to combine environmental and socioeconomic variables. Weights were determined using the Analytical Hierarchy Process (AHP) and Fuzzy logic was applied to model the variables. Our approach was able to identify areas with satisfactory suitability levels for landfills, both serving a large and a small number of municipalities while minimizing social-environmental impacts. This approach is important as it may help directs governmental entities to a appropriate selection of an area within their regional boundaries. We also recommend the proposed method for other regions and locations.
Uma nova estratégia para definir áreas para aterros sanitários consorciados baseados em análise multicritério
Keywords: Analytical Hierarchy Process; Environmental Impact; Fuzzy Logic; Solid Waste